Interprofessional Approach to Increase Billable Care-Events in a Rural Community - Geoffrey A Twigg; John Motsko; Jeff Sherr; Sara El-Baff (University of Minnesota Libraries Publishing, 2017)
Objectives: The study was designed to build a financially stable, replicable, and interprofessional program around a Center of Excellence (COE) model exclusively in a community pharmacy setting. This involved creating a separate pharmacy-based clinic within the community pharmacy with recognized rendering providers by payers allowing pharmacists to bill incident to for services and increase the quality of patient clinical outcomes. Setting: Apple Discount drugs in Salisbury, MD is a multi-site independent community pharmacy setting offering traditional pharmacy services along with several pharmacist run clinical programs. Practice Innovation: The pharmacy developed an interprofessional team around a Center of Excellence (COE) model as a separate medical clinic within the community pharmacy as a subsidiary of the parent company that was staffed with healthcare providers that are recognized by payers to bill for services. Main Outcome Measures: Outcomes of the study included analysis of the number of patients seen, the ability to obtain reimbursement for the clinical services offered, and changes in A1C and BMI to support the clinical value of pharmacist intervention. Results: A total of 309 patients with diabetes were seen over a 16 month period, including 120 patients who completed the 10 hour diabetes training program. Clinical outcomes showed an improvement in A1C from 9.1 pre enrollment to 7.5 post intervention, and a drop in BMI from 35.7 pre enrollment to 32.4 post intervention. The pharmacy was also able to increase the amount of reimbursement for services provided. Conclusions: The development of a pharmacy based clinic business model inside of a community pharmacy has increased the amount of clinically billed services for the pharmacy. Improvements in clinical outcomes led to an acceptance of the pharmacist as a member of the patient's care team by patients, local physician's offices, and third party payers. Funding: This work was supported by the Community Pharmacy Foundation [grant #143 , 2015]   Type: Commentary